TITIK TEMU PERSPEKTIF KH. AHMAD DAHLAN DAN KH. HASYIM ASY’ARI TERHADAP PENDIDIKAN NASIONALIS AGAMIS DI INDONESIA: (Study Literasi terhadap pemikiran Perspektif KH. Ahmad Dahlan Dan KH. Hasyim Asy’ari Terhadap Pendidikan Nasionalis Agamis Di Indonesia) - Thamrin, Mohammad (MEDIAKOM, 2024)
This type of research is literacy research to dissect the intellectual qualities and struggles of the founder of Muhammadiyah (KH. Ahmad Dahlan) and the founder of Nahdlatul Ulama (KH. Hasyim Asy’ari). This research is focused on exploring the intellectual treasures that have been produced by Indonesian educational figures in the past regarding the relationship between nationalism and religion. The approach used in this research is a Historical-Sociological approach. The analysis was carried out using interpretation, internal coherence and comparison methods. This research starts from the assumption that among the emphases of the various treasures of thought of past Indonesian educational figures is an emphasis on the spirit of nationalism-religion. From the results of a study of thinking. K.H. Ahmad Dahlan, and K.H. It is known to Hasyim Asy’ari that even though the social setting in which the educational thinking of these two educational figures emerged is the same, namely the colonial context, they have different paradigms about how education should be implemented. K.H. Ahmad Dahlan saw that Dutch political policies and the existing education system at that time were unfavorable for efforts to revive Islam and liberation from the shackles of colonialism. From here emerged the idea of modernizing Islamic education. K.H. Hasyim Asy’ari sees that the modernization of Western-style education can fade religious values and noble cultural values of the nation which can weaken the fighting spirit against colonialism. From here emerged the spirit of traditionalism. K.H.’s thoughts Ahmad Dahlan has a high commitment to the development of nationalism through the development of progressive Islamic education and eliminating the dichotomy between santri and non-santri. While K.H.’s thoughts Hasyim Asy’ari has a high commitment to the development of nationalism through building national morals based on Islamic religious values and national culture.